WorldSkills International and Its Place in Higher Education System - A. V. Kirichenko; M. N. Strikhanov (Высшее образование в России)
The article discusses the results of the impact of WorldSkills International Movement on the development of national higher education. The authors analyze the main stages of its development, the results of the implementation of WorldSkills standards in the Russian higher education system, dwell on the procedure for the formation of the system of competences that increase the competitiveness of modern specialists. The article includes algorithms for conducting demonstration WorldSkills standards exam, and makes the case for integrated studies to identify trends in the formation and development of professionalism in various activities, develop models of successful specialist, as well as use diagnostic technology to assess his/her personal and professional qualities. In addition, the authors show the relevance of educational innovation through the adaptation of WorldSkills system in conjunction with the modification of training system, and multiplying a promising experience and transfer it to different occupations.